2012
DOI: 10.1155/2012/962347
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide Production and Secretion in Inflammation

Abstract: Gene expression and secretion of the cardiac polypeptide hormones atrial natriuretic factor (ANF) and brain natriuretic peptide (BNP) are simultaneously upregulated in various cardiac disorders such as congestive heart failure, ischemic heart disease, and hypertensive heart disease, in which hemodynamic or neuroendocrine changes are key components in the progression of disease. However, during acute cardiac allograft rejection, plasma BNP levels are increased but not those of ANF. Successful treatment of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 71 publications
2
36
0
Order By: Relevance
“…This elevation was initially reported to be related to cardiac dysfunction, and recently has been reported as a diagnostic marker, predictor of CAL, or predictor of resistance to treatment . Elevation in NT‐proBNP is generally caused by cardiac dysfunction, but may also result from the action of inflammatory cytokines according to reports from the fields of immunology and cardiac transplantation …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This elevation was initially reported to be related to cardiac dysfunction, and recently has been reported as a diagnostic marker, predictor of CAL, or predictor of resistance to treatment . Elevation in NT‐proBNP is generally caused by cardiac dysfunction, but may also result from the action of inflammatory cytokines according to reports from the fields of immunology and cardiac transplantation …”
Section: Discussionmentioning
confidence: 98%
“…NT‐proBNP has also been reported as a diagnostic marker, a predictor of CAL or resistance to treatment, or an index of heart failure . Although BNP or NT‐proBNP elevation is generally caused by mainly left ventricular (LV) overload under conditions of myocarditis or some other cardiac dysfunction, elevation by inflammatory cytokines has been reported from the fields of immunology and cardiac transplantation …”
mentioning
confidence: 99%
“…The development of these cells is promoted by galectin-3 ( Lgals3 ) [38], produced by macrophages [39], which was up-regulated in sick mice, as well as IL-6 ( Il6 ), which can also support myofibroblast formation [39]. Two additional genes, Nppa and Nppb (natriuretic peptide A and brain natriuretic peptide), were shown to be secreted in response to excessive stretching of cardiomyocytes in cardiovascular disease and myocarditis [40,41] and were also up-regulated in sick HLA-DQ8 BALB/c -Tg mice. Clearly, pro-inflammatory genes were up-regulated simultaneously with weakened anti-inflammatory mechanisms in mice with DCM, in addition to the increased expression of fibrosis- and hypoxia-associated genes (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the cross-sectional design of this study, we were unable to determine the causal relation of this association. It has been previously shown that BNP production can be upregulated by proinflammatory cytokines [22]. Further studies attempting to elucidate the clinical significance of the interaction between the immune and BNP systems are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of hsCRP and IL-6 with poststroke cognitive sequelae remains to be determined. Furthermore, due to bidirectional interactions between BNP and the immune system [22], it is important to simultaneously investigate the clinical value of BNP and immune system biomarkers.…”
Section: Introductionmentioning
confidence: 99%